Unfavorable Structural and Functional Outcomes in Myelin Oligodendrocyte Glycoprotein Antibody–Associated Optic Neuritis. Issue 1 (March 2019) - Jelcic, Ilijas; Hanson, James V. M.; Lukas, Sebastian; Weber, Konrad P.; Landau, Klara; Pless, Misha; Reindl, Markus; Weller, Michael; Martin, Roland; Lutterotti, Andreas; Schippling, Sven
Abstract : Background: Recurrent optic neuritis (rON) associated with myelin oligodendrocyte glycoprotein (MOG)-specific antibodies has been initially reported to show a better clinical outcome than aquaporin-4 (AQP4)-seropositive ON in neuromyelitis optica spectrum disorder (NMOSD). Here, we characterize clinical and neuroimaging findings in severe cases of MOG antibody–positive and AQP4 antibody–negative bilateral rON. Methods: Three male adults with rON (ages 18, 44, and 63 years) were evaluated with optical coherence tomography (OCT), MRI, cerebrospinal fluid (CSF), and serological studies. Results: All patients experienced >7 relapses of ON with severe reduction of visual acuity and partial response to steroid treatment. Optic nerves were affected bilaterally, although unilateral relapses were more frequent than simultaneous bilateral recurrences. Patients were MOG-seropositive but repeatedly tested negative for AQP4 antibodies. OCT showed severe thinning of the peripapillary retinal nerve fiber layer. On MRI, contrast-enhancing lesions extended over more than half the length of the optic nerve. CSF analyses during ON episodes were normal. Severe visual deficits accumulated over time in 2 of 3 patients, despite immunosuppressive therapy. Conclusions: MOG-seropositive and AQP4-seronegative rON may be associated with an aggressive disease course and poor functional and structural outcomes. In contrast to previous reports, the severity and pattern of retinal and optic nerve damage closely resembled phenotypes commonly observed in AQP4-seropositive rON without fulfilling current diagnostic criteria for NMOSD. Abstract : Supplemental Digital Content is Available in the Text.